Ultra-high frequency ultrasound delineated changes in carotid and muscular artery intima-media and adventitia thickness in obese early middle-aged women - Sundholm Johnny KM; Litwin Linda; Rönö Kristiina; Koivusalo Saila B; Eriksson Johan G; Sarkola Taisto (SAGE PUBLICATIONS LTD, 2022)
Obesity is linked to increased arterial size, carotid intima-media thickness and arterial stiffness. The effects of obesity and body composition on muscular artery intima-media and adventitia thickness has previously not been established. The aim of this study was to explore associations between carotid and muscular artery wall layer thickness with body composition and cardiovascular risk factors in early middle-aged women. This is a cross-sectional study including 199 women aged 40 +/- 4 years. Arterial lumen (LD), intima-media (IMT) and adventitia thickness (AT) were measured from carotid, brachial and radial arteries using ultra-high frequency ultrasound (22-71 MHz). Women with obesity had increased IMT in carotid (0.47 vs 0.45 mm), brachial (0.19 vs 0.17 mm) and radial arteries (0.16 vs 0.15 mm) and increased brachial AT (0.14 vs 0.13 mm). In multiple regression models all arterial LD (beta-range 0.02-0.03 mm/kg/m(2)), IMT (beta-range 0.91-3.37 mu m/kg/m(2)), AT (beta-range 0.73-1.38 mu m/kg/m(2)) were significantly associated with BMI. The IMT of all arteries were significantly associated with systolic blood pressure (beta-range 0.36-0.85 mu m/mmHg), attenuating the association between IMT and BMI (beta-range 0.18-2.24 mu m/kg/m(2)). Obese early middle-aged women have increased arterial intima media thickness and brachial artery adventitia thickness compared to non-obese counterparts. The association between BMI and intima-media thickness is partly mediated through blood pressure levels.